Proteomic Analysis of Two Different Methods to Induce Skin Melanin Deposition Models in Guinea Pigs - Song F; Wang Y; Wei XG; Yang N; Sun W; Li K; Ma H; Mu J (Dove Medical Press, 2023)
Fei Song,1,2,* Yan Wang,1,* Xiao-ge Wei,1,2 Nan Yang,1 Wenjing Sun,1 Kaiying Li,1 Huisheng Ma,1,2 Jing Mu1 1College of Traditional Chinese Medicine, Ningxia Medical University, Yinchuan, Ningxia, People's Republic of China; 2Key Laboratory of Modernization of Minority Medicine, Ministry of Education, Ningxia Medical University, Yinchuan, Ningxia, People's Republic of China*These authors contributed equally to this workCorrespondence: Jing Mu; Huisheng Ma, Email mujing930@163.com; madoctor@163.comObjective: In this study, we analyzed the differential expression and key signaling pathways of proteins in the skin of guinea pigs with melanin deposition caused by two different modeling methods by utilizing proteomics techniques.Methods: Guinea pig skin melanin deposition models were: (1) induced by ultraviolet (UV) irradiation alone (U group), (2) induced by UV combined with progesterone injection (P group), and guinea pigs treated without any treatment were used as blank group (B group). H&E staining and Masson staining were used to observe the extent of skin damage and melanin deposition in guinea pigs. The differentially expressed proteins (DEPs) in the skin tissues of melanin-deposited guinea pigs were screened by proteomic techniques, the functions of DEPs were analyzed, and a protein-protein interaction network (PPI) was constructed.Results: There was a significant difference in grayscale between the U and P groups of guinea pig skin before and after modeling (P < 0.01). H&E and Masson staining showed that the U and P groups both exhibited incomplete keratinization of the stratum corneum, increased proliferation of epidermal cells with large nuclei and disordered arrangement, neovascularization of the dermis, and increased the number of melanin particles in the epidermis of the U and P groups of guinea pigs compared with the B group. Proteomics analysis showed that there were 171 DEPs between the U and P groups. These DEPs focused on biological processes such as fibrillar collagen trimer, extracellular matrix containing collagen proteins, metalloproteinase activity, and peroxidase activity.Conclusion: The melanin pigmentation model induced solely by UV radiation negatively regulates biological processes such as extracellular matrix and collagen synthesis, while inducing significant skin photoaging. The combination of progesterone injections and UV radiation-induced melanin pigmentation model can cause abnormal protein expression in fatty acid and phospholipid metabolism, possibly being closer to the environment of melasma formation.Keywords: melasma, skin melanin, melanin deposition, ultraviolet, progesterone